Long Non-Coding RNAs as Molecular Biomarkers in Cholangiocarcinoma - Wu, Yanhua; Hayat, Khizar; Hu, Yufei; Yang, Jianfeng (Frontiers in Cell and Developmental Biology, 2022)
Cholangiocarcinoma (CCA) is a biliary system cancer that has the characteristics of strong invasiveness, poor prognosis, and few therapy choices. Furthermore, the absence of precise biomarkers for early identification and prognosis makes it hard to intervene in the early phase of initial diagnosis or recurring cholangiocarcinoma following surgery. Previous studies found that long non-coding RNA (lncRNA), a subgroup of RNA that is more than 200 nucleotides long, can affect cell proliferation, migration, apoptosis, and even drug resistance by altering numerous signaling pathways, thus reaching pro-cancer or anti-cancer outcomes. This review will take a retrospective view of the recent investigations into the role of lncRNAs in cholangiocarcinoma progression and the potential of lncRNAs to serve as promising clinical biomarkers and therapeutic targets for CCA.